The rapidly metabolized 32,000-dalton polypeptide of the chloroplast is the "proteinaceous shield" regulating photosystem II electron transport and mediating diuron herbicide sensitivity. - Mattoo, A K (1981)
Mild trypsin treatment of Spirodela oligorrhiza thylakoid membranes leads to partial digestion of the rapidly metabolized, surface-exposed, 32,000-dalton protein. Under these conditions, photoreduction of ferricyanide becomes insensitive to diuron [3-(3,4-dichlorophenyl)-1,1-dimethylurea], an inhibitor of photosystem II electron transport. Preincubation of thylakoids with diuron leads to a conformational change in the 32,000-dalton protein, modifying its trypsin digestion and preventing expression of diuron insensitivity. Finally, light affects the susceptibility of the 32,000-dalton protein to digestion by trypsin. In other experiments, thylakoids specifically depleted in the 32,000-dalton protein were found to be deficient in electron transport at the reducing side of photosystem II but not at the oxidizing side or in photosystem I activities. Thus, the rapidly metabolized 32,000-dalton thylakoid protein in Spirodela chloroplasts fulfills the requirements of the hypothesized "proteinaceous shield" [Renger, G. (1976) Biochim. Biophys. Acta 440, 287-300] regulating electron flow through photosystem II and mediating diuron sensitivity.